Human-associated migration of Holarctic Saccharomyces uvarum strains to Patagonia. (December 2020) - Gonzalez Flores, Melisa; Rodríguez, María Eugenia; Peris, David; Querol, Amparo; Barrio, Eladio; Lopes, Christian Ariel
Abstract: The domestication of Saccharomyces cerevisiae, as the result of its adaptation to human-manipulated processes, has been well analyzed by both phenotypic and genomic approaches. However, in other yeast species with industrial applications, such as Saccharomyces uvarum, these studies are very limited. To deepen knowledge about possible domestication in S. uvarum, an analysis of the genetic diversity of a series of S. uvarum strains isolated from different habitats was performed. Our results show that the greatest S. uvarum population diversity worldwide is observed in Patagonia, where strains of this species can be isolated from industrial and traditional fermentations as well as from natural environments. This greater Patagonian diversity is due to the presence of strains belonging to two genetically differentiated populations, South America B (SA-B), and Holarctic/South America A (H/SA-A). The H/SA-A population of Patagonia is directly related to apple fermentation environments, mainly from cider fermentations but also, to a lesser extent, from traditional apple chicha. Our data suggest that strains from the Holarctic population colonized Patagonia. This is possibly associated with the introduction of apple trees by European immigrants, since the Spanish colonization of Chile in the 16 th century and the introduction of new apple tree cultivars in the upper valley of the Negro River, Argentina, during the 19 th century. During this process of colonization, Holarctic strains hybridized with SA-B yeasts, generating a series of admixed strains, mainly present in the traditional apple chicha fermentations. Graphical abstract: Image 1